A new cost-effective type of off-street city public transport as a solution to the problem of traffic jams in a large metropolis of Kazakhstan, the city of Almaty - Rakhimbaiev, A. B.; Kabasheva, M. R.; Kalgulova, R. Zh.; Rukavyshnikov, Yu.; Рахімбаєв, А. Б.; Кабашева, М. Р.; Калгулова, Р. Ж.; Рукавишников, Ю. В. (Харківський національний автомобільно-дорожній університет, 2023)
The world today is characterized by a new stage in the development of the scientific and technological revolution, associated with the search for alternative and renewable energy sources, one of which is green energy. In this vein, there is a search for alternative off-street modes of transport which do not use hydrocarbon raw materials. This article discusses the need to use the passenger cable car (PCC) as a full-fledged public transport in the largest metropolis of the Republic of Kazakhstan, the city of Almaty with a population of 2 million people. In 2030 perspective, the number of city residents is expected to increase to 2.5-3.0 million. The city itself is located in the mountain basin of the Trans-Ili Alatau Tien Shan and has exhausted its territorial expansion opportunities in its central part. The personal transport fleet amounted to 700 thousand cars in 2022, of which 230 thousand were the cars from the suburbs [1]. The road network is overloaded with hours-long traffic jams during rush hours, public transport being clearly unable to cope with its functions of delivering passengers. These trends are typical for most megacities around the world. Therefore, new, more efficient solutions have become necessary, and transport network specialists remembered the old aerial cable cars (ACC).
Новий рентабельний вид позавуличного міського громадського транспорту як рішення проблеми заторів у великому мегаполісі Казахстану місті Алмати
Keywords: light rail transit; passenger cable car; cost; Onai card; легкорельсовий транспорт; підвісна пасажирська канатна дорога; собівартість; карта «Онай»; 338.47; 10.30977/PPB.2226-8820.2023.31.112